Priming Your Environment for Growth Through a Collaborative Model of Instructional Coaching - Farr, Wendy; Saltmarsh, Sarah (Educational (Re)naissance, 2018)
Teacher preparation is complex in nature. Students in K-12 education comprise an increasingly culturally and linguistically diverse population. Standards have significantly evolved with state and Common Core State Standards that now place a greater emphasis on academic discourse both in written and oral forms. To better prepare the next generation of teachers to address these shifts in expectations, we are examining the influence of instructional coaching at the university level. The work encompasses professional development on research-based ELL principles to support the changing populations of students in conjunction with coaching sessions to enhance coursework. The results of this study were statistically significant and have set the stage for our next steps in sustainable change at the university level.